Effect of processing route and parameters on the dielectric properties of the valence compensated composition Sr0.65La0.35Ti0.65Co0.35O 3 - Dwivedi R.K.; Parkash O.; Christopher C.C.; Kumar D.; Pandey L. (My University, 2025)
[No abstract available]